A Platform Based Business Revolution Activates Indonesia's Digital Economy - Vivi Meilinda; Sheila Aulia Anjani; M Ridwan (Startupreneur Business Digital (SABDA Journal), 2023)
In the past twenty years, the rise of the internet, often known as e-commerce, has been extremely rapid. The rise of a digital economy was then influenced by this phenomenon. This tendency will revolutionize people's lives in the long run as well as how business, commerce, and the economy develop. Although not all of them are able to grow as large as businesses that have become examples of international success, it can be seen that the development of the many startup companies that are beginning to blossom in Indonesia closely follows this trend. In the past twenty years, the rise of the internet, often known as e-commerce, has been extremely rapid. The rise of a digital economy was then influenced by this phenomenon. This tendency will revolutionize people's lives in the long run as well as how business, commerce, and the economy develop. Although not all of them are able to grow as large as businesses that have become examples of international success, it can be seen that the development of the many startup companies that are beginning to blossom in Indonesia closely follows this trend.